2017
DOI: 10.1136/bjophthalmol-2017-310504
|View full text |Cite
|
Sign up to set email alerts
|

Developing standards for the development of glaucoma virtual clinics using a modified Delphi approach

Abstract: Use of a modified Delphi approach has provided consensus agreement for the standards required for the development of virtual clinics to monitor glaucoma in the UK. It is anticipated that this document will be useful as a guide for those implementing this model of service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The Delphi technique used in this study successfully developed a consensus among the experts contributing through repeated information exchange and feedback ( 28 ). Unlike with the classic Delphi technique, the modified Delphi method used here did not apply the conventional 4 rounds ( 29 31 ). The consultation ended after 2 rounds, as the experts had reached a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…The Delphi technique used in this study successfully developed a consensus among the experts contributing through repeated information exchange and feedback ( 28 ). Unlike with the classic Delphi technique, the modified Delphi method used here did not apply the conventional 4 rounds ( 29 31 ). The consultation ended after 2 rounds, as the experts had reached a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…68 A Delphi survey has also been used to define outcome measures for glaucoma effectiveness trials, 69 to ascertain specifications on screening intervention for open angle glaucoma 70 and to develop standards for glaucoma virtual clinics in the UK. 71 In our study, we aimed to rank expected glaucoma surgery complications according to severity. We achieved a high level of consensus in two rounds with a high response rate (80%), which is a strength of this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent literature review on the reporting of hypotony after glaucoma surgery, the authors found that this parameter had been inconsistently defined across 128 studies. 71 They have also concluded that hypotony should be further coded according to clinical significance. In our study, we have described hypotony as either 'early post-operative with no other symptoms', 'persistent low IOP with no other symptoms', 'low IOP and shallow anterior chamber with peripheral iris-corneal touch' or 'hypotony with maculopathy' to reflect the varying grades of severity.…”
Section: Discussionmentioning
confidence: 99%
“…Digital fundus photographs, copies of the visual field plots, and a summary of the patient record which included case history information, slit lamp findings, intraocular pressure (IOP) and pachymetry readings, and the optometrist's written record of the optic disc assessment, were made available for the consultant to view in a ‘virtual clinic’, similar to that described by Trikha, et al . and Kotecha, et al . following the patient's GRR exam.…”
Section: Methodsmentioning
confidence: 99%